PEMBINAAN SPIRITUAL KOMUNITAS MUALAF BADUY LEBAK BANTEN - Kosim Kosim; Siti Aisyah; Izul Islamudin (Journal of Humanity Dedication, 2026)
Spiritual development is an important process in strengthening the understanding, appreciation, and practice of Islamic teachings among convert communities, including the Baduy Muslim convert community. The Baduy convert community has unique social and cultural characteristics that require adaptive, persuasive, and sustainable guidance approaches. This community service activity was carried out to provide spiritual development for the Baduy Muslim convert community in order to strengthen their Islamic faith. The method of this community service was conducted through the delivery of educational materials and discussions for both parents and children. The materials provided began with educational screenings of Islamic films about the stories of Prophet Ibrahim and Prophet Ismail for the children, and studies of the book Nasoihul Ibad for the parents. The results of this activity showed an increase in children’s motivation to study religion, supported by the distribution of the Qur’an, Juz Amma, Iqro, and other reading books. In addition, the program also provided religious understanding for parents, which helped enhance their spirituality.